Predictors of the antibody response to influenza vaccination in older adults with type 2 diabetes. Issue 1 (13th October 2015) - McElhaney, Janet E; Garneau, Hugo; Camous, Xavier; Dupuis, Gilles; Pawelec, Graham; Baehl, Sarra; Tessier, Daniel; Frost, Eric H; Frasca, Daniela; Larbi, Anis; Fulop, Tamas
Abstract : Objective: Type 2 diabetes mellitus (T2DM) is one of the most prevalent chronic inflammatory diseases of the elderly. Its development is related to the alteration of the immune system with aging characterized by immunosenescence and inflamm-aging. In turn, T2DM also alters the immune response. As a consequence, older people with T2DM are more susceptible to influenza and to its complications as compared with healthy controls. Vaccination against influenza has shown poor efficacy in the older population and even less efficacy in patients with diabetes. We studied here the antibody response to vaccination in healthy and diabetic elderly participants. Research design and methods: In 2 groups of elderly participants (healthy N=119 and T2DM N=102), we measured the immunogenicity of influenza vaccine by hemagglutination inhibition assays. We assessed several blood and functional parameters as potential predictors of the vaccine efficacy. Results: We found no difference between antibody responses in diabetic elderly compared with healthy elderly. Among the biological and functional determinants, the cytomegalovirus (CMV) serostatus played a more prominent role in determining the magnitude of response. We concluded that in addition to age and diabetic status, immunological history such as CMV status should be taken into account. None of the other biological or functional parameters studied could be reliably linked to the vaccine antibody response in older adults who are not frail including those with well-controlled diabetes. Conclusions: Our data strongly suggest that influenza vaccine should be administered to elderly patients with T2DM; however, the immune determinants of the antibody response to influenza vaccination should be further investigated.